Generation and energy exchange of charge states in organic molecular crystoline scintillators - Tarasenko, O.A. (Functional Materials, 2012)
This paper discusses the physical processes that determine the aspects of generation and energy exchange of charge states, which arise in molecular organic media by an action of ionizing radiations of different types. The semi-empirical description of the primary processes of energy exchange in the track of ionizing particles is analyzed. This description takes into account the primary influence of the polarization processes on the charge states energy exchange and quenching processes. The process of quenching is determined by the very fast initial recombination of the molecular polaron pair. This process, at least, is an order of magnitude faster than the process of diffusion expanding of the track, and its efficiency increases with the density of the recombining pairs. The analysis is based on the results of the measurements of the light yield of stilbene and p-terphenyl scintillation detectors as the function of energy for the cases of alpha-, neutron- and gamma excitations. We have studied structurally perfect organic single crystals, hot-pressed polycrystals and composite scintillators. The obtained results testify about the primary influence of the type of ionizing radiation in comparison with the influence of the matter structure.This paper discusses the physical processes that determine the aspects of generation and energy exchange of charge states, which arise in molecular organic media by an action of ionizing radiations. The primary energy loss of a charged ionizing particle in the regions of high density of excitation and the possible causes of this effect are considered.